2004
DOI: 10.1111/j.1462-2920.2004.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

High overall diversity and dominance of microdiverse relationships in salt marsh sulphate‐reducing bacteria

Abstract: The biogeochemistry of North Atlantic salt marshes is characterized by the interplay between the marsh grass Spartina and sulphate-reducing bacteria (SRB), which mineralize the diverse carbon substrates provided by the plants. It was hypothesized that SRB populations display high diversity within the sediment as a result of the rich spatial and chemical structuring provided by Spartina roots. A 2000-member 16S rRNA gene library, prepared with delta-proteobacterial SRB-selective primers, was analysed for divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 94 publications
8
70
0
Order By: Relevance
“…The dominating presence of Desulfobacter biomarkers in all controls, with a low abundance of Desulfobulbus and no evidence of Desulfovibrio is consistent with SRB distribution reported previously in salt marshes. Desulfobacteriaceae associated sequences accounted for over 80% of the recovered sequences, while less than 1% out of 1650 sequences were assigned to Desulfovibrio in a salt marsh study (Klepac-Ceraj et al, 2004). The dominance of Desulfobacteriaceae in salt marsh communities has also been confirmed by other groups (Devereux et al, 1996;Rooney-Varga et al, 1998).…”
Section: Discussionsupporting
confidence: 50%
“…The dominating presence of Desulfobacter biomarkers in all controls, with a low abundance of Desulfobulbus and no evidence of Desulfovibrio is consistent with SRB distribution reported previously in salt marshes. Desulfobacteriaceae associated sequences accounted for over 80% of the recovered sequences, while less than 1% out of 1650 sequences were assigned to Desulfovibrio in a salt marsh study (Klepac-Ceraj et al, 2004). The dominance of Desulfobacteriaceae in salt marsh communities has also been confirmed by other groups (Devereux et al, 1996;Rooney-Varga et al, 1998).…”
Section: Discussionsupporting
confidence: 50%
“…Only a few studies have revealed the microdiversity of free-living bacterial populations (1,29,42,45). The investigated PnecC population differed from these populations in a low microdiversity and a strongly uneven population structure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Acinas et al (1) demonstrated by the construction and analysis of 16S rRNA clone libraries that a coastal bacterioplankton community contained a very high diversity of ribotypes, the vast majority of which fell into phylogenetically microdiverse sequence clusters (Ͻ1% divergent 16S rRNA sequences). Similarly, extensive microdiversities were also observed in populations of sulfate-reducing bacteria inhabiting a salt marsh (29) and in a Vibrio splendidus population from coastal bacterioplankton (42). The V. splendidus population consisted of at least a thousand distinct genotypes, which demonstrated a high variability in genome size and allelic composition (42).…”
mentioning
confidence: 83%
“…This has only recently become possible but has already revealed fine-scale patterns of differentiation within ribotype sequences, which suggest prevalence of natural clusters with 1% internal sequence divergence. In both coastal bacterioplankton and marsh sediment sulphate-reducing bacteria samples, most sequences fell into such microdiverse sequence clusters indicating predominance of closely related taxa (Acinas et al 2004;Klepac-Ceraj et al 2004). Indeed, it has been proposed that sequence clusters may represent natural units of differentiation equivalent to populations or species (Cohan 2002).…”
Section: Patterns Of Microbial Diversitymentioning
confidence: 99%